Analisis Penentuan Harga Pokok Produksi pada UMKM U&Mie Menggunakan Metode Full costing - Kiki Septia Ihwan; Alifa Ilmi; Muhammad Agung Purnama; Yuni Astuti Tri Tartiani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the economy by creating jobs and fostering local economic growth. However, MSMEs, especially in the culinary sector, often face challenges in managing finances, including accurately calculating the Cost of Goods Manufactured (COGM). COGM, which includes raw materials, labor, and overhead costs, is essential for setting appropriate prices and maintaining profitability. Miscalculations can lead to inaccurate pricing, impacting competitiveness and profit margins. This study analyzes COGM calculations at U&Mie, a culinary MSME known for its chili oil chicken noodles, to understand its pricing strategy. Findings from this research and prior studies by Harefa and Purwanto reveal that the full-costing method provides consistent results, highlighting the need for comprehensive COGM calculations to avoid overlooking variables that could affect pricing. This study aims to offer guidance for MSMEs in managing production costs and setting prices effectively, enhancing their market competitiveness.